Social representations in the "social arena" - De Rosa, Annamaria Silvana (Cultural dynamics of social representation., 2012)
Social Representations in the 'Social Arena' presents key theoretical issues and extensive empirical research using different theoretical and methodological approaches to consider the value of social representation theory when social representations are examined in real world contexts.This comprehensive text brings together international experts to explore the relevance of a variety of applications of social representation theory in both institutional and organizational settings, and discusses how social representation theory compares with other constructs of social psycholo.